Combinatorial optimization with photonics-inspired clock models - Mostafa Honari-Latifpour; Matthew S. Mills; Mohammad-Ali Miri (Communications Physics, 2022)
Physics-inspired algorithms are being developed to solve NP-hard problems while alleviating issues with scaling and trapping in local minima. Here, a method to search the global minimum of the Potts Hamiltonian with a photonic-inspired model is proposed.